2020
DOI: 10.3390/cancers12092416
|View full text |Cite
|
Sign up to set email alerts
|

Systems Biology Approaches Reveal Potential Phenotype-Modifier Genes in Neurofibromatosis Type 1

Abstract: Neurofibromatosis type (NF1) is a syndrome characterized by varied symptoms, ranging from mild to more aggressive phenotypes. The variation is not explained only by genetic and epigenetic changes in the NF1 gene and the concept of phenotype-modifier genes in extensively discussed in an attempt to explain this variability. Many datasets and tools are already available to explore the relationship between genetic variation and disease, including systems biology and expression data. To suggest potential NF1 modifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 79 publications
(52 reference statements)
0
5
0
1
Order By: Relevance
“…Concerning the specific genotype/phenotype correlation, apart from the whole‐gene deletions, which show the known high frequency of cognitive impairment (Figure 2), 16 the rate of complications or neoplasms presents a wide range (Table 2), regardless of the type of variant (truncating or non‐truncating): for example, the p.Met992del in‐frame deletion, which is expected to generate a milder phenotype, 7 resulted in our study in a breast cancer at 35 years of age. Although breast cancer is part of the neoplastic spectrum of the Neurofibromatosis I disease, 43 the high genetic heterogeneity of this neoplasm does not rule out in the specific case the possible contribution of different genetic predisposition factors or the role of other modifier genes in the phenotypic expression of the disease 44 . Also the data on the p.Arg1947*, which is reported with a milder phenotype, 45 are only partly confirmed, since we have found 2 tumors (one rhabdomyosarcoma at 19 year of age and one hypothalamic astrocytoma at 12) out of the 14 patients harboring the variant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning the specific genotype/phenotype correlation, apart from the whole‐gene deletions, which show the known high frequency of cognitive impairment (Figure 2), 16 the rate of complications or neoplasms presents a wide range (Table 2), regardless of the type of variant (truncating or non‐truncating): for example, the p.Met992del in‐frame deletion, which is expected to generate a milder phenotype, 7 resulted in our study in a breast cancer at 35 years of age. Although breast cancer is part of the neoplastic spectrum of the Neurofibromatosis I disease, 43 the high genetic heterogeneity of this neoplasm does not rule out in the specific case the possible contribution of different genetic predisposition factors or the role of other modifier genes in the phenotypic expression of the disease 44 . Also the data on the p.Arg1947*, which is reported with a milder phenotype, 45 are only partly confirmed, since we have found 2 tumors (one rhabdomyosarcoma at 19 year of age and one hypothalamic astrocytoma at 12) out of the 14 patients harboring the variant.…”
Section: Discussionmentioning
confidence: 99%
“…Coy number variants are not reported, due to the absence of incident cases in the study population. The shaded areas indicate the 95% confidence intervals contribution of different genetic predisposition factors or the role of other modifier genes in the phenotypic expression of the disease 44.…”
mentioning
confidence: 99%
“…Pathophysiologically, the disease is characterized by a mutation within the NF1 gene that leads to the absence of neurofibromin, which has a tumor suppressor role, leading to the increased RAS activity and subsequent oncogenic potential [ 63 ]. Therefore, the RAS gene itself or its products may represent potential therapeutic targets in neurofibromatosis via two possible directions: either direct inhibitors of the RAS gene or inhibitors of the products resulting from the modulation pathways of RAS [ 64 , 65 ].…”
Section: Treatmentmentioning
confidence: 99%
“…Several large familial NF-1 studies revealed that unlinked modifier genes may influence the expression of the disease ( 36 , 37 ). Recently, using a systems biology strategy, Kowalski et al ( 38 ) identified 10 candidate modifier genes related to the NF-1 phenotype, namely AKT1, BRAF, EGFR, LIMK1, PAK1, PTEN, RAF1, SDC2, SMARCA4 , and VCP . What's more, D'Amico et al ( 39 ) identified that gain-of-function and hypomorphic variants in PTPN11 , a positive regulator of RAS, have been shown to worsen and mitigate, respectively, the severity of the NF1 phenotype.…”
Section: Discussionmentioning
confidence: 99%